Do Vietnamese domestic firms benefit from foreign direct investment? - TU, Nguyen Anh (KDI School, 2015)
FDI has widely been regarded as one of the main drivers of productivity of domestic companies in many developing countries. This thesis will examine the impacts of technology spillovers including horizontal and vertical effects on productivity of manufacturing and non-manufacturing local firms in Vietnam. Using panel firm-level data from 2000 – 2006, It provides evidence of meaningful positive horizontal and negative coefficient of backward linkages in manufacturing sector whereas among non-manufacturing sector, foreign equity participation is not statistically correlated with productivity. The reason for negative backward linkages can be explained by the fact that foreign companies mainly import their inputs from oversea and put local firms in a situation of losing total sales. The thesis, then, tests how the degrees of ownership and firm’s size influence to technology spillovers. It also investigates whether absorptive capacity of local firms facilitates spillovers from FDI. Interestingly, the results show that R&D has negative effects on productivity of domestic firms. One explanation could be “disruptive technology” which at first requires adjustment costs and imposing negative effects on firm’s performance and then helping them have better productivity later.
Thesis(Master) --KDI School:Master of Public Policy,2015